Effect of Occupational Health and Safety (K3) Program on Employee Productivity at PT. Luwu Raya Petroleum City of Parepare - Anastasia D'Ornay (Universitas Muhammadiyah Makassar, 2022)
The objectives of this research are (1) Occupational Health and Safety partially affect employee productivity at PT. Luwu Raya Petroleum, Parepare City. (2). Occupational Health and Safety simultaneously affect the performance of employees at PT. Luwu Raya Petroleum City of Parepare. The data collection techniques in this study were observation, interviews, documentation and literature studies and then processed using the SPSS.25 analysis method. In this study, the population is the employees of PT. Luwu Raya Petroleum, Parepare City, totaling 63 people. In order for this study to provide generalizations with a very small error rate, and considering the total population of 63 people, this study used a sampling technique, namely saturated sampling (census). Thus the number of samples in this study was 63 people. The results of this study indicate that (1) Health (X1) has a positive (0.282) and significant (0.003 0.05) effect on the performance of PT. Luwu Raya Petroleum, Parepare City. (2). Safety (X2) has a positive (0.488) and significant (0.000 0.05) effect on the performance of PT. Luwu Raya Petroleum, Parepare City. (3). Occupational Health and Safety has a positive and significant effect (0.000 0.05) simultaneously on employee performance on the performance of employees of PT. Luwu Raya Petroleum, Parepare City. The result of the coefficient of determination or R Square (R2) is 0.772 which means that the independent variable, namely Health and Safety is able to explain the dependent variable, namely Productivity of 77.2% while the remaining 22.8% is explained by other factors not included in the model. this research